Effect of 5-methylcytosine on the stability of triple-stranded DNA--a thermodynamic study. - Xodo, L E (1991)
We have previously shown that the pyrimidine oligonucleotide 5'CTTCCTCCTCT (Y11) recognizes the double-helical stem of hairpin 5'GAAGGAGGAGA-T4-TCTCCTCCTTC (h26) by triple-helix formation (1). In this paper, we report the effect on triplex formation of substituting the cytosine residues of Y11 with 5-methylcytosines (5meY11). In addition, we have studied the thermodynamics of the interaction between h26 and 5meY11. The results can be summarised as follows: (i) gel electrophoresis shows that at T = 5 degrees C and pH 5, both Y11 and 5meY11 form DNA triple helices with h26, whereas at pH 6.8 only the methylated strand binds to h26; (ii) pH-stability curves of the DNA triplexes formed from h26 + Y11 and h26 + 5meY11 show that Y11 and 5meY11 are semi-protonated at pH 5.7 and 6.7, respectively. Thus, it is concluded that cytosine methylation expands the pH range compatible with triplex formation by one pH unit; (iii) as the unmethylated triplex (h26:Y11), the methylated one (h26:5meY11) denatures in a biphasic manner, in which the low temperature transition results from the dissociation of 5meY11 from h26. The Tm of the triplex to h26 plus 5meY11 transition is strongly enhanced (about 10 degrees C) by cytosine methylation. A van 't Hoff analysis of denaturation curves is presented; (iv) DSC experiments show that triplex formation between 5meY11 and h26 is characterized by delta H = -237 +/- 25 kJ/mol and delta S = -758 +/- 75 J/Kmol, corresponding to an average delta H of -21 kJ/mol and delta S of -69 J/Kmol per Hoogsteen base pair; (v) the thermodynamic analysis indicates that the extra stability imparted to the triplex by methylcytosine is entropic in origin.